El capital humano y su incidencia en el crecimiento económico de ecuador, período: 2006 - 2016. - Borja, María Eugenia (2017)
The present research work called human capital and its impact on economic growth in Ecuador during the period 2006 - 2016, focuses on analyzing investment in strategic sectors such as health and education as mechanisms that constitute a priority for economic growth and social welfare. The content of the research is composed of four chapters as follows: Chapter I. - Reference Frame, refers to the problem statement, problem formulation, general and specific objectives, and justification and importance; In this chapter we can highlight the problem that arises the research and the objectives that it is desired to fulfill to demonstrate the importance of the same. Chapter II. - Theoretical Framework, is composed of concepts, characteristics, theories, as well as the approaches that determine the behavior of the same, just as economic growth is considered principles, sources and theories. Chapter III. - Methodological Framework, describes the methodology applied in research, health indicators and educational indicators, the economic growth behavior and the results of the estimation of the econometric model, through the linear regression model estimated by the method of ordinary least squares. Chapter IV. - The conclusions and respective recommendations of the investigative work are presented.